Demographic effects and complications of IUD insertions in the immediate post-abortal period - Iglesias, Solina R. 1941- (1977)
Abstract

This study was undertaken to evaluate the demographic effectiveness and safety of IUD insertions in the immediate post-abortal period. This was the first of its kind to be conducted in the Philippines.
The experiences of immediate post-abortal IUD acceptors were examined
against those of immediate postpartum IUD acceptors and post-abortal
non-acceptors. It was discovered that although IUD insertions in the immediate postpartum period produced better results, IUD insertions in the immediate post-abortal period compared favorably with other IUD insertions in the Philippine family planning program in terms of continuation rates.
It was likewise shown that IUD insertions in the immediate post-abortal period caused no serious complications although slightly more side-effects were reported by immediate post-abortal than postpartum acceptors.
A comparison was made between survey data and clinic data. It was found that continuation rates based on clinic data were inflated because of under-reporting of termination events as a result of a very low rate of return visit to the clinic.
Another important finding was the fact that IUD had helped reduce the fertility of its users. The percentage fertility decline among acceptors was definitely higher than among non-acceptors.

Finally, a theoretical comparison was made between immediate IUD insertion and immediate sterilization of limiters. It was found that immediate sterilization was far superior to IUD insertions because it can avert at least twice as many births as immediate IUD insertion.
Vita.
Thesis (Master of Arts in Demography)
Keywords: Intrauterine contraceptives